The role of the body in the experience of installation art: a case study of visitors' bodily, emotional, and transformative experiences in Tomás Saraceno's “in orbit” - Kühnapfel, Corinna; Fingerhut, Joerg; Pelowski, Matthew (Frontiers in Psychology, 2023)
Installation art, with its immersive and participatory character, has been argued to require the use and awareness of the body, which potentially constitute key parts of the artwork's experience and appreciation. Heightened body awareness is even argued to be a key to particularly profound emotional or even transformative states, which have been frequently ascribed to this genre. However, the body in the experience of installation art has rarely been empirically considered. To address this gap, we investigated the body's role in the experience of Tomás Saraceno's in orbit installation. Based on a list of self-report items created from a review of the theoretical literature, we—for the first time—captured (quantitatively and qualitatively): what kind of subjective bodily experiences visitors (N = 230) reported, how these items grouped into clusters (using network science), and how these relate to emotion, art appraisal, and transformative outcomes. Network analysis of the items determined four communities related to “interoception,” “presence,” “disturbance,” and “proprioception.” Proprioception (e.g., awareness of balance/movement/weight) turned out to be a significant determinant of art appreciation in our study, and, together with “disturbing” body experiences (feeling awkward/watched/chills), coincided with transformation. We also assessed individual differences in body awareness yet did not find that these moderate those relationships. We suggest future research on installation art based on a more unified assessment of the role of the body in embodied-enactive aesthetics and its relation to the intensity and impact of art experience in general.